Description Of The Level Of Anxiety In The Use Of Anti-Tuberculosis Drugs (OAT) In Pulmonary TB Patients At RSU. Imelda Medan - Silaban, Nataria Yanti; Naibaho, Eka Nugraha V; Siburian, Christine Handayani (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
Pulmonary TB or tuberculosis is an infectious disease caused by rod-shaped bacteria, namely Mycobacterium tuberculosis. (WHO, 2011). Pulmonary tuberculosis can spread to almost any part of the body, including the meningens, kidneys, bones, and lymph nodes. The initial infection usually occurs within 2 to 10 weeks after exposure, then it can form active disease due to a decreased or inadequate immune system response. The purpose of this study is an overview of the level of anxiety in the use of anti-tuberculosis drugs (OAT) in TB patients. Lungs in RSU. Imelda Medan. This type of research is descriptive with a total of 30 respondents. The results of the study based on age characteristics obtained the majority aged 50-54 as many as 16 respondents (53%), for the majority of male gender as many as 20 respondents (66.67%), the majority of education educated DIII as many as 14 respondents (47%). Based on the characteristics of the level of anxiety, it showed that of the 30 respondents, the majority of mild anxiety was 14 respondents (46.7%), and the minority of respondents were poorly informed as many as 2 respondents (6.7%).